A White Matter Fiber Microdissection Study of the Anterior Perforated Substance and the Basal Forebrain: A Gateway to the Basal Ganglia?. Issue 3 (24th November 2018) - Serra, Carlo; Akeret, Kevin; Maldaner, Nicolai; Staartjes, Victor E; Regli, Luca; Baltsavias, Gerasimos; Krayenbühl, Niklaus
Abstract: BACKGROUND: Studies detailing the anatomy of the basal forebrain (BF) from a neurosurgical perspective are missing. OBJECTIVE: To describe the anatomy of the BF and of the anterior perforated substance (APS), the BF emphasizing surgical useful anatomical relationship between surface landmarks and deep structures. METHODS: White matter fiber microdissection was performed on 5 brain specimens to analyze the topographic anatomy of the APS and expose layer-by-layer fiber tracts and nuclei of the BF. RESULTS: The APS, as identified anatomically, surgically, and neuroradiologically, has clear borders measured 23.3 ± 3.4 mm (19-27) in the mediolateral and 12.5 ± 1.2 mm (11-14) in the anteroposterior directions. A detailed stratigraphy of the BF was performed from the APS up to basal ganglia and thalamus allowing identification and dissection of the main components of the BF (septum, nucleus accumbens, amygdala, innominate substance) and its white matter tracts (band of Broca, extracapsular thalamic peduncle, ventral amygdalohypothalamic fibers). The olfactory trigone together with diagonal gyrus and the APS proper is a relevant superficial landmark for the basal ganglia (inferior to the nucleus accumbens, lateral to the caudate head, and medial to the lentiform nucleus). CONCLUSION: The findings in our study supplement available anatomic knowledge of APS and BF, providing reliable landmarks for precise topographic diagnosis of BF lesions and for intraoperative orientation. Surgically relevant relationships between surface and deep anatomic structures are highlighted offering thus a contribution to neurosurgeons willing to perform surgery in this delicate area.